FAO/IBPGR technical guidelines for the safe movement of yam germplasm - Brunt, A.A.; Jackson, G.V.H.; Frison, Emile A.; Food and Agriculture Organization of the United Nations; International Plant Genetic Resources Institute (1989)
These guidelines are divided into 2 parts. The first makes general recommendations on how best to move Dioscorea germplasm and mentions available intermediate quarantine facilities. The second part covers the important insect and nematode pests and viral and fungal diseases of quarantine concern. The information given on any particular pest or pathogen concentrates on those aspects most relevant to quarantine. (Abstract © CAB ABSTRACTS, CAB International)